The noise of time [large type] - Barnes, Julian (Thorndike Press Large Print, 2016)
This compact masterpiece dedicated to the Russian composer Dmitri Shostakovich is both a stunning portrait of a relentlessly fascinating man and a brilliant meditation on the meaning of art and its place in society.